Generational Travel Behavior and Sustainable Tourism Preferences in Contemporary Tourism Development - I Ketut Candra (Bali Tourism Journal, 2026)
The tourism industry is undergoing profound transformation driven by demographic shifts, digital innovation, and increasing awareness of sustainability. Understanding how different generations perceive and experience tourism has become essential for developing adaptive and sustainable tourism strategies. This study aims to analyze generational travel behavior and explore its implications for sustainable tourism development by examining the travel preferences of Baby Boomers, Generation X, Millennials, and Generation Z. A qualitative literature review was employed, synthesizing recent academic studies, tourism reports, and policy publications published between 2020 and 2026. The collected literature was analyzed using thematic analysis to identify recurring patterns related to travel motivations, sustainable tourism preferences, technological adoption, and multigenerational travel dynamics. The findings reveal that younger generations, particularly Millennials and Generation Z, prioritize authentic experiences, cultural immersion, digital connectivity, environmental responsibility, and wellness-oriented travel. In contrast, Generation X and Baby Boomers place greater emphasis on comfort, safety, accessibility, and family-oriented experiences, while increasingly supporting sustainable tourism when appropriate infrastructure and services are available. The study also highlights the growing influence of digital technologies, including social media, artificial intelligence, and personalized travel platforms, in shaping destination choice and tourist behavior across generations. Furthermore, the emergence of multigenerational travel creates opportunities for value co-creation, family bonding, and inclusive tourism product development. These findings suggest that tourism stakeholders should adopt differentiated marketing strategies, strengthen sustainable destination management, promote community participation, and develop inclusive tourism experiences that accommodate diverse generational needs. By integrating demographic, technological, and sustainability perspectives, this study contributes to the growing body of knowledge on contemporary tourism behavior and offers practical insights for policymakers, destination managers, and tourism businesses seeking to foster resilient, competitive, and sustainable tourism development.